Evaluate some complex motor performances in the final game of volleyball between Egypt and Tunisia in the African qualifiers - Qualifying for the Olympics, Rio de Janeiro, Brazil, 2016 - Kandil, S. M. (International Journal of Sports Science and Arts, 2020)
Aim of the research: Identify performances motor composite most widely and commonly used in the final game of volleyball between Egypt and Tunisia in the African qualifying for the Olympics, Rio de Janeiro, Brazil, 2016 as following:1-receiving of the area front and rear (direct receiving by foot - direct receiving head - receiving By arms from the bottom by passing for striking - receiving By arms from the bottom to pass it to an existing preparing - receive direct pass to the playground competitor - receiving from the top by passing the striking - receiving from the top by passing the prepared).2-Scrolling from the frontal and rear: (direct scrolling playground competitor - the scroll from the top of the front hit the front - the scroll from the top to hit back - preparation from the bottom of the hit). 3-Beating of frontal and rare: (beating of the scroll from the top of the front - the beating of scrolling back higher - beating of preparation from the bottom) First conclusions: The most important motor composite performances in the receiving directions:performances motor composite in region front (receiver By arms pass it from the bottom of the preparer) the positions (3-4), and (receiving from the top by passing the preparer) positions (2-3-4)performances motor composite in region background (receivers By arms pass it from the bottom of the contagious - Receiving for direct pass to competitor playground -receiving from the top by passing the preparer) positions play (1-6-5)The most important composite performances kinetic scrolling directions:performances motor composite in front of the area scrolling directions (scroll from the top of the front beaten- scroll from the top to the back behind a beaten) positions play (2-3)performances composite kinetic scrolling in the background of the area directions (pass from the top of the front hit the front - direct scrolling playground competitor - the scroll from the top to the back behind a beaten) players position (6)The most important trends performances in the motor composite beatings:performances motor composite trends in beatings of the frontal area (beating of the scroll from the top of the front - beatings of scrolling back up) for players positions (3), (4)First: performances motor composite in the directions of the area beatings the background (beatings of scrolling back up) and play position (1)Second: motor performance composite (beating of the scroll from the top of the front) to play position (1)Third, composite motor performance (beatings of the numbers from the bottom) positions (1), (5).